Cognitive improvement after cochlear implantation in deaf children with associated disabilities. (11th September 2020) - Micheletti, Serena; Accorsi, Patrizia; Giordano, Lucio; Calza, Stefano; Nassif, Nader; Barezzani, Maria G; Fazzi, Elisa; Redaelli de Zinis, Luca O
Abstract : Aim: To monitor functional auditory and non‐verbal cognitive skills in children with cochlear implants who had associated disabilities over a 24‐month period and define how cochlear implantation may impact on non‐verbal cognition by restoring functional auditory skills. Method: Sixty‐four children with cochlear implants (36 females, 28 males; mean age 4y 3mo, SD 3y 5mo, 9mo–14y 5mo) were recruited and divided into three groups: children with typical development group (TDG); children with associated disabilities not linked to non‐verbal cognitive disorders group (ADG1); and children with associated disabilities linked to non‐verbal cognitive disorders group (ADG2). Tests of functional auditory, communicative, and non‐verbal cognitive skills were performed before cochlear implantation and at 12 and 24 months after cochlear implantation. Results: Functional auditory and communicative skills improved similarly in the three groups at 12 and 24 months after implantation. An increase in non‐verbal cognitive scores was present in children in the ADG2 from baseline to 12 and 24 months ( p <0.01), whereas scores remained stable in children in the TDG and ADG1. The increased functional auditory skills scores after cochlear implantation corresponded to an increase in non‐verbal cognitive scores ( p =0.032) in children in the ADG2. Interpretation: Children with associated disabilities, especially if linked to non‐verbal cognitive disorders, benefitted from cochlear implantation. They improved their comprehension of acoustic information inferred from the environment, improving not only functional auditory skills but also non‐verbal cognition. Abstract : This article is commented on by Meinzen‐Derr on page 1348 of this issue.